Ankle Sprain Injuries: A 2-Year Prospective Cohort Study in Female Greek Professional Basketball Players - Kofotolis, Nikolaos (National Athletic Trainers Association, 2007)
Context: Ankle sprains are a common basketball injury. Therefore, examination of risk factors for injury in female professional basketball players is worthwhile. Objective: To examine rates of ankle sprains, associated time missed from participation, and risk factors for injury during 2 consecutive seasons. Design: Prospective cohort study. Setting: Eighteen professional basketball facilities. Patients or Other Participants: We observed 204 players from 18 female professional basketball teams for 2 consecutive seasons during a 2-year period. Main Outcome Measure(s): Using questionnaires, we recorded the incidence of ankle sprains, participation time missed, and mechanisms of injury in games and practice sessions. Potential risk factors, such as age, body mass, height, training experience, and history of ankle sprain, were examined using multivariate logistic regression. Results: Fifty of the 204 participants sustained ankle injuries; injuries included 32 ankle sprains, which translated to an ankle sprain rate of 1.12 per 1000 hours of exposure to injury. The 32 players missed 224.4 training and game sessions and an average of 7.01 sessions per injury. Most injuries occurred in the key area of the basketball court and were the result of contact. Injury rates during games were higher than injury rates during practice sessions. Centers, followed by guards and forwards, had the highest rate of injury. Players who did not wear an external ankle support had an odds ratio of 2.481 for sustaining an ankle sprain. Conclusions: Female professional basketball athletes who did not wear an external ankle support, who played in the key area, or who functioned as centers had a higher risk for ankle sprain than did other players.